2016
DOI: 10.3389/fpsyg.2016.01360
|View full text |Cite
|
Sign up to set email alerts
|

How People's Motivational System and Situational Motivation Influence Their Risky Financial Choices

Abstract: People's preferences for risks have been a subject of interest to researchers in both the economy and psychology fields over the last few years. This has given rise to many important findings about the role of psychological factors that influence people's choices. The presented studies focused on the role of motivational systems (described by Higgins in the Regulatory Focus Theory) in explaining people's financial choices. The main goal was to examine the relationship between people's chronic promotion and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Children with induced promotion focus decided to save more often, while children with induced prevention focus chose immediate consumption more often. Previous research (Sekścińska et al 2016) revealed that both promotion and prevention orientations may support saving, but Cho et al (2014) showed that the final effect of regulatory focus on saving behaviour may depend largely on the regulatory fit between motivation of the person and the type of saving goal (promotion vs. prevention). Promotion goals relate to nurturance and growth needs (e.g., saving for buying/investing in one's own business, saving for travels, saving for buying a house, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Children with induced promotion focus decided to save more often, while children with induced prevention focus chose immediate consumption more often. Previous research (Sekścińska et al 2016) revealed that both promotion and prevention orientations may support saving, but Cho et al (2014) showed that the final effect of regulatory focus on saving behaviour may depend largely on the regulatory fit between motivation of the person and the type of saving goal (promotion vs. prevention). Promotion goals relate to nurturance and growth needs (e.g., saving for buying/investing in one's own business, saving for travels, saving for buying a house, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that both promotion and prevention foci may facilitate saving behaviour but may have different consequences for the ways of delaying consumption. Recent research (Sekścińska et al 2016) showed that a higher level of promotion motivation was associated with the preference to delay consumption. The same preference presented people with higher prevention motivation.…”
Section: Regulatory Focus In Economic Decisionsmentioning
confidence: 99%
See 3 more Smart Citations